Death and violence on the reservation: homicide, family violence, and suicide in American Indian populations - Bachman, Ronet (Auburn House, 1992)
This volume is the first major attempt to systematically examine the etiology of violence in American Indian communities. Using fieldwork as well as quantitative and qualitative research, Bachman first presents an overview of American Indians from historical and contemporary perspectives, before she focuses specifically on violence and its causes. Homicide, suicide, and family violence are analyzed in depth, and the destructive impacts of alcohol and other addictive substances are documented.||Dr. Bachman effectively uses personal stories and narratives given by American Indians to illustrate